2004
DOI: 10.1063/1.1682700
|View full text |Cite
|
Sign up to set email alerts
|

Carrier trapping and current collapse mechanism in GaN metal–semiconductor field-effect transistors

Abstract: A mechanism for current collapse in GaN metal–semiconductor field-effect transistors is proposed, which assumes the existence of acceptor traps with multiple states in the band gap. Current collapse has been experimentally observed in the current–voltage characteristic after the drain voltage sweep had exceeded the threshold for impact ionization in a previous measurement. In the proposed model, electrons generated by impact ionization are captured by neutral acceptor trap states in the substrate located above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…It should be mentioned that current collapse was not observed in the first measurement at Vbs = 0 V. However, current collapse was observed in subsequent measurements if the drain bias was over 30 V in previous measurements. As explained by the present authors, the observed characteristics can be explained by identifying acceptor traps with dual-energy states [15]. In GaN, the impurity responsible for carrier trapping that leads to dc current collapse has not been identified; however, it is highly likely that it is due to C, which may introduce multiple states within the band gap, and we refer to the two states as X++"'' and X+"'" in this analysis.…”
Section: B Determination Of Trap-related Circuit Parametersmentioning
confidence: 94%
See 1 more Smart Citation
“…It should be mentioned that current collapse was not observed in the first measurement at Vbs = 0 V. However, current collapse was observed in subsequent measurements if the drain bias was over 30 V in previous measurements. As explained by the present authors, the observed characteristics can be explained by identifying acceptor traps with dual-energy states [15]. In GaN, the impurity responsible for carrier trapping that leads to dc current collapse has not been identified; however, it is highly likely that it is due to C, which may introduce multiple states within the band gap, and we refer to the two states as X++"'' and X+"'" in this analysis.…”
Section: B Determination Of Trap-related Circuit Parametersmentioning
confidence: 94%
“…Calculated I-V characteristics, as shown in Fig. 2, are based upon a physical mechanism for current collapse and restoration proposed by the present authors in [15]. At high drain bias, the electrons are captured by the traps located in the substrate, forming a second depletion layer in the channel at the channel-substrate interface as shown in the inset of Fig.…”
Section: Gan-based Heterojunction Field Effect Transistors (Fets)mentioning
confidence: 99%
“…This phenomenon is caused by negative fixed charges on the device surface [3] and/or in the AlGaN and GaN layers [4], as illustrated in Fig. 2.…”
Section: Current Collapsementioning
confidence: 99%
“…This phenomenon is caused by negative fixed charges on the device surface 31) and/or in the AlGaN and GaN layers. 32,33) The negative charges reduce the 2DEG density in the drift region, which results in an increased on-resistance. The surface charges are redistributed from the gate owing to the high electric field concentration at the gate edge.…”
Section: Current Collapsementioning
confidence: 99%